2015
DOI: 10.1111/acel.12338
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Slow Aging in Humans: Are We Ready?

Abstract: The workshop entitled ‘Interventions to Slow Aging in Humans: Are We Ready?’ was held in Erice, Italy, on October 8–13, 2013, to bring together leading experts in the biology and genetics of aging and obtain a consensus related to the discovery and development of safe interventions to slow aging and increase healthy lifespan in humans. There was consensus that there is sufficient evidence that aging interventions will delay and prevent disease onset for many chronic conditions of adult and old age. Essential p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
384
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 502 publications
(404 citation statements)
references
References 181 publications
(253 reference statements)
3
384
0
2
Order By: Relevance
“…This may in part explain why they held promise as treatments to improve insulin resistance and type 2 diabetes. AMPK has also been suggested to control the aging process in general (Salminen & Kaarniranta, 2012), and targeting AMPK has been discussed as a potential strategy to slow down aging in humans (Longo et al, 2015). Interestingly, ASA has recently been revealed as a lifespan‐extending treatment in both mice and nematodes (Ayyadevara et al, 2013; Strong et al, 2008; Wan, Zheng, Wu, & Luo, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This may in part explain why they held promise as treatments to improve insulin resistance and type 2 diabetes. AMPK has also been suggested to control the aging process in general (Salminen & Kaarniranta, 2012), and targeting AMPK has been discussed as a potential strategy to slow down aging in humans (Longo et al, 2015). Interestingly, ASA has recently been revealed as a lifespan‐extending treatment in both mice and nematodes (Ayyadevara et al, 2013; Strong et al, 2008; Wan, Zheng, Wu, & Luo, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Whether there is some specificity to the effects of restriction of different essential amino acids is still under debate (Longo et al., 2015). Therefore, the amino acid profiles of homogenates of kidney samples obtained from the four groups of aged mice were evaluated, to identify an amino acid that might be responsible for the adverse effects of EEA supplementation in the diet‐restricted aged mice.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decades, scientific studies on aging have demonstrated that genetic modulation can extend lifespan in diverse model organisms and have established that aging can be targeted by dietary and pharmacologic interventions (Longo et al., 2015). Metformin, the most widely used antidiabetic drug in the world, has been reported to favorably influence metabolic and cellular processes closely associated with the development of aging and even to delay aging in animal models (Novelle et al., 2016).…”
Section: Discussionmentioning
confidence: 99%